Design of Passive Backscattering RFID-Devices - Seemann, Kay; Huemer, Mario (Elektrotechnik und Informationstechnik, 2005)
The endeavors in realizing ubiquitous chips for ambient intelligence networks increased significantly over the past few years. In particular, the passive radio frequency identification (RFID) technology became a well known synonym for passive transponder devices. The increased attention is not only related to economical advantages, but also to the general technological potential. This article deals with the design of self-sustaining wireless transponders based on the backscattering technology. We explain the general architecture, present important design constraints and emphasize general characteristics of the backscattering radio-frequency (RF) front-end approach. Furthermore, we extend the common linear models by some important nonlinear figures of merit.
elib2cris::1512001600,seemann2005c